Diversidad y recambio de especies de anfibios y reptiles entre coberturas vegetales en una localidad del valle del Magdalena medio, departamento de Antioquia, Colombia (2016)
From December 2012 and January 2013 a survey of the herpetofauna diversity was made in forest remnants, farms, open areas, and vegetation around wetlands at a locality in the middle Magdalena River valley, department of Antioquia, Colombia. We recorded 27 amphibian and 36 reptile species. Three of the amphibian species are endemic to Colombia and one is considered threatened; one of the reptile species is endemic to Colombia, and three are categorized as threatened. The species diversity of amphibians and reptiles did not differ significantly between forest and farming areas, but it was higher than in open areas and vegetation associated with wetlands. The species turnover between these two groups of vegetation coverages was higher in amphibians than in reptiles. This differential species turnover level suggests that forest amphibians are more susceptible than the reptiles to deforestation, possibly due to their high dependence of moist microhabitats. Since most forests in the Middle Magdalena River valley of Colombia have been deforested, the conservation of forest remnants that still persist is a priority.